Low-Cost Audience Polling Using Computer Vision - Cross, Andrew; Cutrell, Ed; Thies, Bill (UIST, 2012)
Electronic response systems known as “clickers” have demonstrated educational benefits in well-resourced classrooms, but remain out-of-reach for most schools due to their prohibitive cost. We propose a new, low-cost technique that utilizes computer vision for real-time polling of a classroom. Our approach allows teachers to ask a multiple-choice question. Students respond by holding up a qCard : a sheet of paper that contains a printed code, similar to a QR code, encoding their student IDs. Students indicate their answers (A, B, C or D) by holding the card in one of four orientations. Using a laptop and an off-the-shelf webcam, our software automatically recognizes and aggregates the students’ responses and displays them to the teacher. We built this system and performed initial trials in secondary schools in Bangalore, India. In a 25-student classroom, our system offers 99.8% recognition accuracy, captures 97% of responses within 10 seconds, and costs 15 times less than existing electronic solutions.